Fishing Ground Ikan Layang (Decapterus spp) di Perairan Utara Aceh - Febri, Suri Purnama; Iskandar, Budhi Hascaryo; Simbolon, Domu; Harahap, Antoni (Jurnal Ilmiah Samudra Akuatika, 2022)
Accurate determination of fishing zone gives an abundance result of fish capturing. However, fishermen in the north water of Aceh have difficulties in deciding such position and are resulting to the minimum yields. This thesis uses MODIS satellite imaging to overcomes such problem by (1) determining the spreading and SPL variation, and a-chlorophyll in the north water of Aceh, (2) finding the composition quantity and size of fish (Decapterus spp.) from fishing zone, and (3) predicting fishing zone in the north water of Aceh. This study uses survey methodology consist of field data (in-situ) and satellite image data (ex-situ). It is performed by three steps, (1) field surveying in the study location, (2) collecting field data, and (3) downloading SPL image and a-chlorophyll from MODIS satellite. Results found that relationship between SPL and a-chlorophyll toward yields and sizes are non linear, with least square (R2) of about 0.012 and 0.002. Furthermore, SPL and chlorophyll are varied in each seasonal period at the range from 27.53oC to 29.05oC and from 0.20 mg/m3 to 0.26 mg/m3. Sizes of fish captured using purse seine are not complying with the current standard and are included under category of restricted to be captured. Fishing ground Indian Scad (decapterus spp) in North water of Aceh on Pulo Beras and is a potential area, while Sabang, Pulo Nasi, Lhok Nga, Laot Aceh dan Peukan Bada included to medium potential area.